Teenage daughters' view on their parents' influence in their clothing behaviour - Etulle, Eden Patricia P.
ABSTRACT Clothing behavior can be a good reference in measuring how parents influence their daughters. The general objective of this research was to know how selected Filipino female teenagers clothing behaviour is influenced by their parents. The study specifically aimed to describe the clothing behaviour of these teenagers, determine if they think that their clothing behaviour are influenced by their parents, and to identify what values these parents consider as they influence their daughters' clothing behaviour. The study uses the descriptive research design. An interview questionnaire was used to gather qualitative data. A sample of 31 female residents of the Kalayaan Residence Hall in the U.P. Diliman campus were selected through convenience sampling. Only 83.87% or 26 of the respondents said their clothing behaviour is influenced by their parents. Among the clothing behaviour categories, it was in the category of "practices followed during purchase decision" where a greater percentage of respondents (76.92%) said that they were influenced by their parents in that category. There was a greater percentage of respondents who said that they were not influenced by their parents in that category. There was a greater percentage of respondents who said that they were not influenced by their parents in the other five clothing behaviour categories - clothing choice criteria, clothing interests, views on clothing, and appearance management. Parents consider aesthetic values the most as they influence their daughters' clothing behaviour in the categories of clothing choice criteria, clothing interests, and appearance management. On the other hand, they consider economic values as they influence their daughter's clothing behaviour in terms of practices during purchase decision. Further studies on male teenagers and studies relating clothing behaviour to specific Filipino family values are recommended.